2000
DOI: 10.1103/physrevlett.84.4842
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the Elusive Zonal Flow Using Cross-Bicoherence Analysis

Abstract: We show that the modulational instability growth rate of zonal flows is determined directly from the quasilinear wave kinetic equation. We also demonstrate the relation between zonal-flow growth and the cross bispectrum of the high-frequency drift-wave-driven Reynolds stress and the low-frequency plasma potential by explicit calculation. Experimental measurements of the spatiotemporal evolution of the spectrum integrated bicoherence at the L-->H transition near the edge shear layer indicate a modification in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
125
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 22 publications
8
125
0
Order By: Relevance
“…Similar ZFs have also been seen in spontaneous H-mode. [6][7][8][9]19,20 Our results appear thus to support the significance of ZFs and LDC in improved-confinement regimes.…”
Section: Long-distance Correlation and Zonal Flow Structures Induced supporting
confidence: 70%
See 1 more Smart Citation
“…Similar ZFs have also been seen in spontaneous H-mode. [6][7][8][9]19,20 Our results appear thus to support the significance of ZFs and LDC in improved-confinement regimes.…”
Section: Long-distance Correlation and Zonal Flow Structures Induced supporting
confidence: 70%
“…5 Such ZFs might thus also be important ingredients in regulating turbulence and hence take part in explaining the transition from low to high ͑L-H͒ confinement regimes. [6][7][8][9] Investigations into ZFs have been intensified recently, both theoretically and experimentally as reviewed in Refs. 10 and 11.…”
Section: Long-distance Correlation and Zonal Flow Structures Induced mentioning
confidence: 99%
“…It is interesting to note that such process is reminiscent of the zonal flow creation (Drake et al, 1992) observed in tokamak in relation with the L-H transition (Diamond et al, 2000).…”
Section: Velocity Shearsmentioning
confidence: 99%
“…For example, an interpretation of bispectral functions has been discussed in Refs. [15,22]. In a previous article [19], the bispectral analysis of the edge fluctuation data in the JFT-2M tokamak [23] (limiter configuration) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis has been applied to various plasma experiments [12][13][14][15][16][17][18][19][20] and has contributed much to the understanding of, e.g., the nonlinear interaction among drift wave turbulence, the Reynolds-stress drive for zonal flows, the onset of the high-confinement mode (H-mode) transition, and so on. In addition, the reality of the zonal flow has been confirmed experimentally [21], and the need for bispectral analysis has increased.…”
Section: Introductionmentioning
confidence: 99%